Clinical outcomes of near-infrared photoimmunotherapy according to immune checkpoint inhibitor timing and treatment sequence: a multicenter retrospective study - Takuma Makino; Shohei Fujimoto; Yorihisa Orita; Tomoyasu Tachibana; Yuto Naoi; Mizuo Ando (International Journal of Clinical Oncology, 2026)
Abstract Background Near-infrared photoimmunotherapy (NIR-PIT) is a novel local treatment for recurrent or metastatic head and neck cancer. However, the clinical significance of immune checkpoint inhibitor (ICI) timing and treatment sequencing remains unclear. This study investigated their association with clinical outcomes after NIR-PIT. Methods This multicenter retrospective study included 44 patients with 48 lesions who underwent initial NIR-PIT between January 2021 and March 2026. The primary analysis compared outcomes according to prior ICI exposure. An exploratory analysis evaluated outcomes according to treatment sequence and timing of ICI administration. The primary endpoint was local control. Secondary endpoints were objective response rate and disease control rate, while overall survival was assessed exploratorily. Results Median local control duration was 253 days, but was 174 days in the prior ICI exposure group and 342 days in the non-prior ICI exposure group (log-rank P = 0.031). Local progression occurred in 69.2–37.1% of lesions, respectively ( P = 0.059). Among 45 evaluable lesions, the objective response rate and disease control rate were 60.0–93.3%, respectively. Median overall survival was 866 days. Exploratory analyses suggested potential differences in clinical outcomes according to treatment sequence and ICI timing. Conclusions Prior ICI exposure was associated with poorer local control after NIR-PIT. Exploratory analyses suggested that ICI timing and treatment sequencing may influence clinical outcomes. Treatment sequencing may represent an important consideration when integrating NIR-PIT and ICIs for recurrent or metastatic head and neck cancer.